PENGARUH RELIGIUSITAS TERHADAP PERILAKU EKONOMI MASYARAKAT PASAR TRADISIONAL (STUDI EMPIRIS PADA MASYARAKAT PASAR TRADISIONAL DI KOTA SERANG PROVINSI BANTEN) - Ma’zumi Ma’zumi; Taswiyah Taswiyah; Najmudin Najmudin (Al Qalam, 2017)
This research oriented to analyze influence of religiosity on the economic behavior of traditional market society in The Serang City of Banten Province. The result of the research could be information, reference, and policy formulation for developing economy, till it achieves on the target, creates individual and social pious. The Method used in the research is causal relationship to determine the level of influence. The technique used in this research is questionnaires contain a set of questions for respondents to answer. While to know the influence of religiosity (X variable) toward economic behavior of traditional market society (Y Variable) in The Serang City of Banten Province. The result of the research showed the influence of religiosity on the economic behavior of traditional market society in the Serang city of Banten Province based on the r square value 81,17 and results for inner weight 48.095. based on the analysis concluded that religiosity has a high influence on the economic behavior (distributor and consumer) compared with other aspects. Keywords: Religiosity, Economic Behavior, Individual and Social Pious